The 1970 yellow fever epidemic in Okwoga District, Benue Plateau State, Nigeria: 3. Serological responses in persons with and without pre-existing heterologous Group B immunity - Monath, T. P. (1973)
Serological studies of persons infected with yellow fever (YF) during the 1970 epidemic in Okwoga District, Nigeria, indicated that epidemic YF occurred despite a high prevalence of pre-existing group B arbovirus immunity, which increased with age. The viruses involved were primarily dengue, Zika, and Wesselsbron. Patterns of responses of haemagglutination-inhibiting, complement-fixing, and neutralizing antibodies in primary YF and in superinfections are defined in this paper.